Starch-Based Fishing Composite Fiber and Its Degradation Behavior - Wenwen Yu; Fei Yang; Lei Wang; Yongli Liu; Jiangao Shi (International Journal of Polymer Science)
The starch-based fishing composite fibers were prepared by one-step reactive extrusion and melt spinning. The effects of starch contents on the microstructural, thermal, dynamic mechanical, and mechanical properties of starch-based composite fibers were studied. And the degradation behaviors in soil of the fibers were also investigated. The compatibility between starch and HDPE is improved significantly by grafting maleic anhydride (MA) using one-step reactive blending extrusion. As the starch content increased, the melting temperature and the crystallinity of the fibers gradually decreased due to fluffy internal structures. Dynamic mechanical analysis showed that the transition peak α in the high-temperature region was gradually weakened and narrowed with increasing starch content; moreover, a shoulder appeared on the low-temperature side of the α peak was assigned to the β-relaxation related to starch phase. In addition, the mechanical results showed the significant decrease in the breaking strength and increase in the elongation at break of the starch-based composite fibers as the starch content increased. After degradation in soil for 5 months, the surface of the composite fibers had been deteriorated, while flocculent layers were observed and a large number of microfibers appeared. And the weight loss rate of the starch-based composite fibers (5.2~34.8%) significantly increased with increasing starch content (50~90 wt%).